Diversity of Hoya Species across Three Plantation Landscapes in Jember Regency and the Phytochemical and Antioxidant Potential of Hoya lacunosa Blume - Ulum, Fuad bahrul; Hayyinah, Asa Hanifatul; Sulistiyowati, Hari; Ratnasari, Tri; Dwinianti, Edia Fitri; Setyati, Dwi; Su'udi, Mukhamad (Universitas Negeri Semarang, 2025)
Jember Regency encompasses several plantation areas characterized by diverse ecological conditions, notably the Gumitir, Garahan, and Tancak plantations. Among the flora in these regions, the genus Hoya is notable for its medicinal potential. This study aimed to characterize the diversity of Hoya species, provide detailed morphological documentation, and evaluate the phytochemical and antioxidant properties of a medicinally used species. Field exploration employed a systematic plot-based design consisting of 150 plots (5 × 5 m²) with 3 m spacing. The most vegetatively dominant species, Hoya lacunosa, was subjected to GC–MS phytochemical analysis and DPPH-based antioxidant evaluation. A total of eleven Hoya species were recorded across the three plantation sites. The Gumitir plantation exhibited the highest diversity, containing ten species., i.e. Hoya burtoniae, H. camphorifolia, H. carnosa, H. cinnamomifolia, H. dennisii, H. fuscomarginata, H. lacunosa, H. micrantha, H. purpureofusca, and two unidentified Hoya spp. In contrast, the Garahan plantation supported only H. dennisii and H. fuscomarginata, while H. lacunosa was exclusively found in Tancak indicating a highly localized distribution. GC-MS profiling on H. lacunosa leaves revealed 26 compounds, comprising 16 secondary metabolites (12 phenolics, 2 alkaloids, and 2 terpenes) and 5 primary metabolites. The methanol extract exhibited strong antioxidant activity (IC₅₀ = 50.89 ppm), reflecting its potential as a natural source of bioactive compounds. These findings demonstrate substantial Hoya diversity in Jember Regency and underscore the potential of H. lacunosa as a valuable source of bioactive metabolites for pharmaceutical development.